Associations between cognitive abilities and 20-year personality changes in older adults in the ILSE Study: Does health matter? - Wettstein, Markus; Tauber, Benjamin; Wahl, Hans-Werner (The journals of gerontology. Series B, Psychological sciences, social sciences, 2020)
Objectives: We used data from the Interdisciplinary Longitudinal Study on Adult Development (ILSE study) to investigate whether associations of cognitive abilities with late-life personality changes are moderated by individuals’ physical health. Method: Individuals born between 1930 and 1932 (n = 473; mean baseline age: 62.87 years) were assessed up to four times over a period of about 20 years (M = 20.34 years). Cognitive abilities were assessed based on multiple tests representing various cognitive functions. In addition, the Big Five personality traits were measured. Study participants’ health was rated by a physician based on several in-depth medical examinations. Results: Health appeared as a significant moderator of the associations between cognitive abilities and personality trajectories: First, lower cognitive abilities were associated with an increase in neuroticism in individuals with poor health, but not in those with good health. Second, lower cognitive abilities were related with an increase in agreeableness in older adults with good health, but with a decrease in agreeableness among those with poor health. Third, better cognitive abilities were associated with stability in conscientiousness, but only among individuals with poorer health. Discussion: Our findings suggest that once health is compromised, cognitive abilities may become a compensatory resource to prevent undesirable personality changes.
Published: 26 December 2018
Gesehen am 12.03.2020